VALUASI EKONOMI OBJEK WISATA HUTAN MANGROVE MUNJANG DI DESA KURAU BARAT KABUPATEN BANGKA TENGAH - Soleha Soleha; Yudi Sapta Pranoto; Evahelda Evahelda (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
This study aims to calculate economic value based on travel costs and environmental services of Mangrove Munjang Forest attractions. This research was conducted in the supporting Mangrove Munjang Forest in Kurau Barat Village, Koba Subdistrict, Central Bangka Regency starting in November 2018 until June 2019. The research method used was the survey method. The sampling method using simple accidental sampling for the determination of 100 respondents obtained using the Rao Purba formula, and the method of analysing travel costs using Pearson Correlation analysis. The results of the study showed that the overall economic value of Mangrove Munjang Forests was Rp28.292.560.968 per year that is the flora value of Rp15.037.827.000, fauna value Rp7.286.730.000, carbon dioxide absorption value is Rp4.261.243.068 and the value of travel cost is Rp1.706.760.900. The correlation between the cost of travel and the number of visits showed a strong relationship namely -,540 with the direction of a negative relationship namely the higher the cost of travel incurred by visitors, the lower the visitor’s desire to travel o tourist attractions and vice versa.